2013
DOI: 10.1007/s11999-013-3120-6
|View full text |Cite|
|
Sign up to set email alerts
|

Local Alendronic Acid Elution Increases Net Periimplant Bone Formation: A Micro-CT Analysis

Abstract: This concept has potential to improve the biologic fixation of porous reconstructive implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…Local application is of particular interest in cases where existing bone needs to be preserved and augmented whilst avoiding the known side effects related to systemic administration [14,15]. Several in vivo studies have shown that a local delivery of BPs can enhance peri-implant bone density [16,17], implant fixation [18e22], and the repair of bony defects [23,24] in animal models and humans. Furthermore BPs have been shown to preserve bone allografts [25,26] as well as bone sites affected by osteonecrosis [27].…”
Section: Introductionmentioning
confidence: 99%
“…Local application is of particular interest in cases where existing bone needs to be preserved and augmented whilst avoiding the known side effects related to systemic administration [14,15]. Several in vivo studies have shown that a local delivery of BPs can enhance peri-implant bone density [16,17], implant fixation [18e22], and the repair of bony defects [23,24] in animal models and humans. Furthermore BPs have been shown to preserve bone allografts [25,26] as well as bone sites affected by osteonecrosis [27].…”
Section: Introductionmentioning
confidence: 99%
“…Alendronate was dissolved in aliquots of distilled deionized water to produce doses of 0.02 mg/cm 2 , 0.06 mg/cm 2 , and 0.18 mg/cm 2 . The 0.06 mg/cm 2 alendronate dose was chosen based on the previous successful results using a similar implant [5]. To find the lowest effective dose, a dose 1 .…”
Section: Implant Structurementioning
confidence: 99%
“…Periimplant bone was defined as the area surrounding the implant. A radius of 2.5 mm from the implant was specified based on a previous study that showed that bone formation that resulted from local bisphosphonate elution was localized to the periimplant region [5]. Periimplant bone was calculated by taking the percentage of bone found in the area of the 2.5 mm radius and dividing this by the total area defined by this medullary space, not including the area of the implant.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations